Hubungan Antara Budaya Organisasi Dan Kepemimpinan Terhadap Kinerja Pengurus KONI Kabupaten Sampang Dalam Rangka Menuju PORPROV JATIM VII Tahun 2022 - Ishma Alfisa Martianto (Jurnal Ilmu Manajemen, 2022)
The main purpose of a company for its employees is to strive to improve employee performance which aims to achieve company goals. To achieve this goal, companies need competent employees to improve their performance. This study analyzes the influence of organizational culture and leadership on the performance of KONI employees in Sampang Regency. This type of research is a quantitative research using a saturated sample technique. The objects used for this research sample are all members of KONI Sampang Regency, totaling 30 respondents. From the results of statistical analysis, this study uses Partial Least Square (PLS) and is assisted by smartPLS 3.0 software. The results of this study based on statistical calculations indicate that the leadership variable has an influence on employee performance and the organizational culture variable has a relationship with leadership. This study implies the form of organizational culture and good leadership that affect employee performance in the work environment.